PENGARUH ALAT PEMASARAN HIJAU TERHADAP PERILAKU PEMBELIAN KONSUMEN - Puspa Dewi, Ni Made Ari; Rahyuda, Ketut (E-Jurnal Manajemen; Vol 7 No 4 (2018)DO - 10.24843/EJMUNUD.2018.v07.i04.p16, 2018)
The phenomenon of increasing awareness and concern for environmental sustainability encourages every individual to consume environmentally friendly products that make the company implement green marketing strategy. One company that implements the green marketing strategy of PT. Martina Berto, Tbk with its products Sariayu Martha Tilaar. The purpose of this study is to determine the effect of green marketing tools in the form of eco label, eco brand, and environmental advertisement and which variables dominantly influence consumer buying behavior of Sariayu Martha Tilaar. This research uses quantitative approach and conducted in Denpasar City. The sample in this study amounted to 112 respondents with non-probability sampling method of purposive sampling technique. Data collection was done through interviews and questionnaires. Data analysis techniques used multiple linear regression. The results of this study indicate that all hypotheses are accepted. Eco label has a positive and significant impact on consumer purchasing behavior. Eco brand has a positive and significant impact on consumer purchasing behavior. Environmental advertisement has a positive and significant impact on consumer purchasing behavior. Eco brand is a variable of green marketing tool that has dominant influence to consumer purchasing behavior.